Dysphagia Relieved by Endoscopic Transpapillary Pancreatic Duct Stent Placement! - Rana, Surinder Singh; Sharma, Ravi; Ahmed, Sobur Uddin; Guleria, Sonali; Gupta, Rajesh (Journal of Digestive Endoscopy, 2019)
Pancreatic fluid collections are usually peripancreatic in location but can be found at various atypical locations such as the mediastinum. Mediastinal pseudocysts are very rare and are very unusual cause of dysphagia. Here, we report a rare case of mediastinal pseudocyst occuring because of pancreatic duct disruption due to chronic pancreatitis and presenting as dysphagia and successfully treated with endoscopic transpapillary stent placement.
Keywords: Chronic pancreatitis; endosonography; pseudocyst; stent